1999
DOI: 10.1089/thy.1999.9.757
|View full text |Cite
|
Sign up to set email alerts
|

Variable Phenotype Associated with Ser505Asn-Activating Thyrotropin-Receptor Germline Mutation

Abstract: Constitutively activating thyrotropin-receptor (TSHR) germline mutations have been identified as a molecular cause of hereditary nonautoimmune hyperthyroidism. To date, seven cases of familial and six cases of sporadic nonautoimmune hyperthyroidism have been described associated with 13 different TSHR germline mutations, with a variable clinical course. We report the case of a 12.3-year-old girl with a history of thyrotoxicosis since the age of 11 months who developed diffuse thyroid hyperplasia at the age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 13 publications
3
32
0
2
Order By: Relevance
“…No correlation with the phenotype of HTNs could be found for the different functional properties of somatic (Arturi et al 1998) or germline (Fuhrer et al 1999) TSHR mutations. Defects in feedback mechanisms such as GRK-induced desensitization of the TSHR receptor are possible explanations for these differences.…”
Section: Expression Of Grk 3 and Grk 4 Is Increased In Htnsmentioning
confidence: 99%
“…No correlation with the phenotype of HTNs could be found for the different functional properties of somatic (Arturi et al 1998) or germline (Fuhrer et al 1999) TSHR mutations. Defects in feedback mechanisms such as GRK-induced desensitization of the TSHR receptor are possible explanations for these differences.…”
Section: Expression Of Grk 3 and Grk 4 Is Increased In Htnsmentioning
confidence: 99%
“…In spite of large variations of the time spans (months to 17 years) for transitions of autonomously functioning thyroid nodules (AFTNs) from subclinical to overt hyperthyroidism (Sandrock et al, 1993;Paschke and Ludgate, 1997), there is no genotype-phenotype correlation for constitutively activating TSHR mutations (Fuhrer et al, 1999), which can be found in 60% of all cases (Parma et al, 1993;Arturi et al, 1998). It is therefore very likely that unknown signaling events, apart from counter-regulatory mechanisms like arrestins (Voigt et al, 2000) or GRKs, contribute to the etiology of AFTNs and the clinical phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Germline mutations in the TSHR have also been identified in familial non-autoimmune hyperthyroidism, in which it displays autosomal dominant inheritance, and in cases of sporadic neonatal thyrotoxicosis, which may become familial in time (18,19). The age of onset of symptoms can vary widely, even in the same family (20).…”
Section: Introductionmentioning
confidence: 99%